18th- and Early 19th-Century Brickmaking at the John Jay Homestead: The Process, Products, and Craftsmen - Feister, L. M.; J. Sopko (Northeast Historical Archaeology, 1996)
On-site brick kilns were established routinely for construction projects at non-urban sites in the 18th and early 19th centuries. Archaeological excavations at the brick lot at the John Jay Homestead State Historic Site revealed features relating to the manufacture of a brick. Documentary and scientific research revealed information about the brickmakers and established a baseline for the identification of brick sources from three different areas of New York State. Comparisons between brickmakers at the Jay and Schuyler houses and between brickmakers and other craftsmen are discussed here.
Keywords: 18th and early 19th centuries; archaeological excavations; brick kilns; John Jay Homestead State Historic Site